A globally accurate potential energy surface and quantum dynamics calculations on the Be(1S) + H2(v0 = 0, j0 = 0) → BeH + H reaction - Yang, Zijiang; Chen, Maodu (Frontiers in Physics, 2022)
The reactive collision between Be atom and H2 molecule has received great interest both experimentally and theoretically due to its significant role in hydrogen storage, astrophysics, quantum chemistry and other fields, but the corresponding dynamics calculations have not been reported. Herein, a globally accurate ground-state BeH2 PES is represented using the neural network strategy based on 12371 high-level ab initio points. On this newly constructed PES, the quantum time-dependent wave packet calculations on the Be(1S) + H2(v0 = 0, j0 = 0) → BeH + H reaction are performed to study the microscopic dynamics mechanisms. The calculated results indicate that this reaction follows the complex-forming mechanism near the reactive threshold, whereas a direct H-abstraction process gradually plays the dominant role when the collision energy is large enough. The newly constructed PES can be used for further dynamics calculations on the BeH2 reactive system, such as the rovibrational excitations and isotopic substitutions of the H2 molecule, and the presented dynamics data would be of importance in experimental research at a finer level.